Numerical simulation of unsteady two‐layered pulsatile blood flow in a stenosed flexible artery: Effect of peripheral layer viscosity - Chakravarty, S.; Mandal, P. K.; Mandal, A. (Mathematical Modelling and Analysis, 2004)
The present paper deals with a theoretical investigation of blood flow in an arterial segment in the presence of stenosis. The streaming blood is treated to be composed of two different layers – the central core and the plasma. The former is considered to be non‐Newtonian liquid characterised by the Power law model, while the latter is chosen to be Newtonian. The artery is simulated as an elastic (moving wall) cylindrical tube. The unsteady flow mechanism of the present study is subjected to a pulsatile pressure gradient arising from the normal functioning of the heart. The time‐variant geometry of the stenosis has been accounted for in order to improve resemblance to the real situation. The unsteady flow mechanism, subjected to pulsatile pressure gradient, has been solved using finite difference scheme by exploiting the physically realistic prescribed conditions. An extensive quantitative analysis has been performed through numerical computations of the flow velocity, the flux, the resistive impedances and the wall shear stresses, together with their dependence with the time, the input pressure gradient and the severity of the stenosis, presented graphically at the end of the paper in order to illustrate the applicability of the model under consideration. Special emphasis has been made to compare the existing results with the present ones and found to have a good agreement.Nestacionaraus dvisluoksnio pulsuojančio kraujo srauto tekėjimas esant stenozei lanksčioje arterijoje skaitinis modeliavimas: periferinio sluoksnio klampumo efektaiSantrauka. Straipsnyje nagrinėjamas kraujo srauto tekėjimas esant stenozei. Nagrinėjamas dvisluoksnis kraujo tekėjimas. Arterija modeliuojama kaip vamzdis su elastinėmis sienelėmis. Kraujo srauto nestacionarumą sukelia širdies veikla. Skaitinis sprendinys randamas baigtinių skirtumų metodu. Atlikta kokybinė skaitinių sprendinių analizė iliustruojanti greičių, srautų, sienelės įtampų priklausomybę laike. Skaitiniai rezultatai pakankamai gerai patvirtina eksperimentinius duomenis.First Published Online: 14 Oct 2010